2018
DOI: 10.1016/j.annepidem.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Measures of human immunodeficiency virus (HIV) community viral load and HIV incidence among people who inject drugs

Abstract: The effect of community VL on HIV incidence may be stronger than previously reported. Future studies of community VL surveillance should consider accounting for the prevalence of HIV using a prevalence-adjusted community VL measure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Kelley and colleagues first proposed the concept of using PDV in a study of men who have sex with men in the United States to capture transmission risk and inequalities in healthcare coverage [ 21 ]. This measure was used in high‐prevalence areas to identify transmission hotspots [ 22 ] and within key population networks [ 23 , 24 ]. Two studies demonstrated its superiority over other metrics to predict HIV incidence [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kelley and colleagues first proposed the concept of using PDV in a study of men who have sex with men in the United States to capture transmission risk and inequalities in healthcare coverage [ 21 ]. This measure was used in high‐prevalence areas to identify transmission hotspots [ 22 ] and within key population networks [ 23 , 24 ]. Two studies demonstrated its superiority over other metrics to predict HIV incidence [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Colombian study [18] showed a strong correlation between increases in ART coverage, decreases in VL at the population level, and decreases in the number of new HIV cases. A study of injecting drug users in San Francisco showed that mean CVL was signi cantly associated with HIV incidence [19], validating the utility of CVLs as a measure of HIV transmission potential. To date, few studies in China have directly compared the level of VL surveillance among different populations in the same sample and analyzed the strength of associations between PVL surrogate measures and indicators related to HIV transmission potential.…”
Section: Introductionmentioning
confidence: 93%